ISLAM DAN WARISAN KESENIAN KESULTANAN PALEMBANG DARUSSALAM - Ryllian Chandra (Fakultas Adab dan Humaniora UIN Raden Fatah, 2018)
This article discusses the interrelationship between Islam and arts in the culture which is inherited from Sultanate of Palembang Darussalam. Islam is often used as the main cause of the lack of art in the original culture of Palembang. The explanation is not satisfactory so another hypothesis is needed to probe and look for other factors that can explain how the construction of Palembang art legacy. Political, economic, and social dynamics influence the presence of art, so religion could not be considered as a barrier to the development of art.